MnO2/CNT as ORR Electrocatalyst in Air-Cathode Microbial Fuel Cells - Chee, Wai Woon; Huei, Ruey Ong; K. F., Chong; Khan, Maksudur R. (Elsevier Ltd., 2015)
Air-cathode microbial fuel cell (MFC) is a potential electrochemical device for green power generation simultaneously conducting wastewater treatment. In the present work, the MnO2 catalyst has been prepared and modified by inducing carbon nanotube (CNT) via sonochemical-coprecipitation method. The as-prepared catalyst (MnO2/CNT) was characterized by x-ray powder diffraction patterns (XRD), field emission scanning electron microscope (FESEM), energy-dispersive x-ray spectroscopy (EDS), transmission electron microscopy (TEM) and cyclic voltammetry (CV) to examine its morphological surface, crystal structure, elemental analysis and oxygen reduction reaction (ORR) activity of the catalyst, respectively. The CV results revealed that MnO2/CNT catalyzed ORR at potential of -0.45 V. The effect of catalyst loading on the chemical oxygen demand (COD) removal efficiency of palm oil mill effluent (POME) and MFC performance were studied. The maximum power density and open circuit voltage (OCV) generated from with the as-prepared MnO2/CNT were measured to be 215.57 mW/m3 and 582 mV, respectively.